Students' Creative Thinking Ability Through Creative Problem Solving based Learning - Baiq Fatmawati; Baiq Miftahul Jannah; Maya Sasmita (Postgraduate, University of Mataram, 2022)
Creative thinking is identified with the thinking process which includes fluency, flexibility, originality and elaboration. This creative thinking habit can be trained by applying a creative problem-solving model, namely learning creative problem solving, this model is one of constructivist learning. The research focus is applying creative problem solving-based learning to students' creative thinking. Participants are students of SMA Negeri 1 Masbagik for the 2019/2020 academic year class X Science. Quasi-experimental research design with post-test-only control design. Collecting data using a description test. Data analysis by t-test and using SPSS 25.0 program application for its calculations. The results of data analysis: 1) the experimental class obtained a significant average value on the indicators of creative thinking fluency (78.00), flexibility (77.00), originality (54.73), 2) fluency control class (60.18), flexibility (55.48), originality (50.18). The conclusion of this research is that creative problem-solving learning has an impact on students' creative thinking in all indicators with an increasing average value in the experimental class